Tantangan Dan Peluang Implementasi E-Government Dalam Meningkatkan Transparansi Dan Akuntabilitas Pemerintahan Desa Di Kabupaten Sinjai - Muhammad Lutfi; Mursak; Muhlis Hajar Adiputra; Fitriani (Jurnal Ilmu Administrasi Negara, 2026)
This study aims to analyze the challenges and opportunities of e-government implementation in improving transparency and accountability in village governance in Sinjai Regency. The research employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, observations, documentation, and Focus Group Discussions (FGD), and analyzed using N-Vivo software. The findings indicate that e-government adoption in villages in Sinjai Regency remains at an early to intermediate stage. Implementation is largely dominated by mandatory applications such as SISKEUDES and SIPADES, along with the use of village websites and social media for information dissemination. The implementation has positively contributed to greater transparency in financial management and village programs, as well as strengthened administrative accountability and public trust. However, several challenges persist, including limited digital infrastructure, low human resource capacity, resistance to change, and budget constraints. Nevertheless, opportunities remain through service system integration, capacity building for village officials and communities, and stronger policy support from the local government. Strengthening these aspects is essential to achieve transparent, accountable, and responsive village governance